2007
DOI: 10.1149/1.2437062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Membrane- and Catalyst-Layer-Thickness Nonuniformities in Polymer-Electrolyte Fuel Cells

Abstract: In this paper, results from mathematical, pseudo 2-D simulations are shown for four different along-the-channel thickness distributions of both the membrane and cathode catalyst layer. The results and subsequent analysis clearly demonstrate that for the membrane thickness distributions, cell performance is affected a few percent under low relative-humidity conditions and that the position along the gas channel is more important than the local thickness variations.However, for the catalyst-layer thickness distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…This is something that has only minimally been studied in the modeling literature. 529,530 In the same fashion, in order to accelerate the components development it is necessary to correlate the measurable properties to the performance effect on a PEFC over its lifetime. This is a place where modeling has a possible significant role to play, since experiments require substantial times to enact.…”
Section: Discussionmentioning
confidence: 99%
“…This is something that has only minimally been studied in the modeling literature. 529,530 In the same fashion, in order to accelerate the components development it is necessary to correlate the measurable properties to the performance effect on a PEFC over its lifetime. This is a place where modeling has a possible significant role to play, since experiments require substantial times to enact.…”
Section: Discussionmentioning
confidence: 99%
“…Although the crossover is normally only a small efficiency loss, it does limit the thickness of the membrane, 78 and can become important if pinholes or membrane thinning occur. Furthermore, crossover is attributed to carbon corrosion during fuel starvation, 49 platinum band formation, 45 and peroxide generation.…”
Section: Other Transport Through the Membranementioning
confidence: 99%
“…This situation was looked at by Weber and Newman,78 through the use of a 1-D model that is run in a 2-D array of node points, where each point was connected to each other through simultaneous mass and energy balances. They found that crossflow increases the average humidity and provides around a 30% increase in current density for 25 % relativehumidity feeds than the coflow case.…”
Section: Gas-flow Directionmentioning
confidence: 99%
“…Given the limited availability and high cost of precious metals such as Pt, optimization of catalyst layer structure is of particular importance for large-scale PEMFC deployment. Evidence exists to show that catalyst layer imperfections such as a spot with restricted metal loading have a substantial effect on both membrane-electrode assembly (MEA) performance and durability [7,8,9]. This shows the importance of studies on catalyst layers in the larger context of PEMFC commercialization.…”
Section: Introductionmentioning
confidence: 99%